2019
DOI: 10.1039/c8cc08280d
|View full text |Cite
|
Sign up to set email alerts
|

Building two-dimensional metal–organic networks with tin

Abstract: We report the first example of a surface-supported 2D metal–organic network with Sn atoms as coordination centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…9,11,18,19,36 One reason for this difference is the fact that TCNQ can form a strong chemical bond with the metal substrate, 22,40,41 and thus the metal substrate actively participates in the MOF formation and may significantly affect the MOF properties. 11,21 Similar effects are not expected on a graphene substrate, where strong chemical interaction with TCNQ does not take place. 42 Even though the graphene-supported M-TCNQ 2D MOFs share the same structures, their stability and thermal decomposition mechanisms are very different.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…9,11,18,19,36 One reason for this difference is the fact that TCNQ can form a strong chemical bond with the metal substrate, 22,40,41 and thus the metal substrate actively participates in the MOF formation and may significantly affect the MOF properties. 11,21 Similar effects are not expected on a graphene substrate, where strong chemical interaction with TCNQ does not take place. 42 Even though the graphene-supported M-TCNQ 2D MOFs share the same structures, their stability and thermal decomposition mechanisms are very different.…”
Section: Resultssupporting
confidence: 60%
“…Here, we present three well-defined and remarkably stable 2D MOFs supported on an inert graphene/Ir(111) substrate. As the organic linker we utilize a TCNQ molecule (7,7,8,8-tetracyanoquinodimethane), which is a strong electron acceptor and a popular choice for MOF synthesis both on-surface 7,9,[18][19][20][21][22] and in solution. 23,24 TCNQ-based 2D MOFs are also intensively studied computationally, [25][26][27][28][29][30][31] but the simulated free-standing systems are not directly comparable to metal-supported nor solution-based MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Figure a shows a domain of the α phase, where the rectangular unit cell ( b 1 α = 11 ± 0.5 Å and b 2 α = 7.4 ± 0.5 Å) is indicated, compatible with a commensurate (3√2 × 2√2) R 45° unit cell and corresponding to a coverage of 1/12 ML. The small intermolecular distance of this arrangement implies that the negatively charged CN groups are facing one each other, which would be energetically unfavorable. ,, Additionally, the unit cell of this phase is very similar to that of the MONs formed by TCNQ with Ni , Mn, and Sn as coordinating atoms on different substrates. We then concluded that the α phase is stabilized by a metal–ligand coordination interaction.…”
Section: Resultsmentioning
confidence: 85%
“…Additionally, TCNQ has been extensively used as an organic ligand in the production of 2D metal–organic networks (MONs) on surfaces with different magnetic, electronic, and structural properties, which are also strongly affected by the choice of the substrate. In the previous reports, the molecules and the metal centers were separately evaporated on the surface. An alternative route to produce MONs is to incorporate atoms or to capture native adatoms directly from the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…34 In this particular case, the Sn-mediated coordination can be discarded since the Cu−nitrile coordination bonds are dominant over the Sn−nitrile bonds. 19,34 The rectangular Mn−TCNQ network, with a Mn:TCNQ ratio of 1:1 and each Mn atom coordinating four TCNQ molecules by their nitrile groups, seems to be the most reasonable candidate for the obtained structure. Although geometrically similar to the RT α phase of Cu−TCNQ, the structure of the Mn− TCNQ unit cell is predicted to be significantly different in terms of adsorption sites and molecular conformation, as will be shown hereafter.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%